Methods of stakeholder prioritisation in the context of stakeholder management - Mints, A. Yu.; Kamyshnykova, E. V.; Мінц, О. Ю. (Vilnius Gediminas Technical University, 2021)
Purpose – the purpose of this paper is to propose a method for integral assessing the priority level of specif-ic stakeholders in the model of stakeholder management. Research methodology – the paper develops ideas of matrix approach to assessing the priority level of individual stakeholders and proposes a method for obtaining more accurate integral assessment based on analysis of a set of indi-cators, taking into account factors of subjective estimates. Findings – the integral assessment of the priority level of specific external stakeholders improves estimates’ accuracy and provides a practical framework for the development of successful corporate social responsibility strategies. It has been substantiated by the application of the proposed method for prioritising suppliers of a large Ukranian metallurgi-cal company. Research limitations – there are requirements for a linear or quasi-linear nature of the relationship between the numer-ical value of the stakeholder’s priority index and its interpretation on a “better to worse” scale within the framework of the proposed method of evaluation. Practical implications – integral assessments of stakeholder priority obtained from the results of the proposed method can be used as a tool for reasonable comparison, selection of strategic stakeholders and building programs for interac-tion with them. Originality/Value – unlike most existing methods of stakeholder analysis representing a generic list of priority stake-holder groups the method proposed in the paper provides an integral assessment of priority level of specific stakehold-ers from the category of the immediate environment through a system of indicators, taking into account factors of sub-jectivity.
Keywords: prioritisation; stakeholder; opportunities; interest; expert assessment